Morphology of the Eye of the Southern Right Whales ( Eubalaena australis ) - Buono, Mónica Romina (2011)
Recently there has been a growing interest in the anatomy and optics of the visual system of cetaceans. However, much of the new information has been focused on odontocetes, and relatively little is known about the visual anatomy of baleen whales. Here, we describe the eye anatomy of the southern right whale (Eubalaena australis). Eye samples were collected from 26 calves, 4 adults with known body length, as well as 2 specimens of unknown body length that had stranded near their nursery ground at Península Valdés, Argentina, over six years. We provide anatomical descriptions of the eyeball and extraocular structures, as well as quantitative data in the form of eyeball, corneal, scleral and lens measurements. In order to explore the sensitivity of the eye to light, the f-number was estimated in one specimen. We found that the eyes of the calves differed from those of the adults in having less periorbital fat surrounding the eyeball. We also observed variations in the abundance of periorbital fat among the adult specimens. The regression analysis revealed a correlation between body length and eyeball size. By contrast, the dimensions of the cornea were only weakly correlated with body length. The estimated f-number suggests that the optical sensitivity of the Eubalaena australis eye is relatively low. However, caution should be taken in interpreting fnumber as a proxy of eye sensitivity because it depends on the lens size, which can be affected by the fixation methods employed.